Definisi Prinsip dan Tujuan Negosiasi Bisnis Pengertian Dasar, Fungsi, dan Sasaran Negosiasi dalam Dunia Usaha - Dinda Ananda Nasution; Dion Alfa Harefa; Intan Sari; Melani Melani; Mayang Sari (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Research on business negotiation is becoming increasingly relevant amid the dynamics of globalization, digitalization, and intense competition that require organizations to have adaptive communication and collaboration strategies. Negotiation no longer serves only as a means of reaching agreement, but also as a strategic mechanism for creating added value, building long-term relationships, and mitigating business risks. This study aims to systematically examine the definitions, principles, functions, and objectives of negotiation based on international and national academic literature from 2015 to 2025. The research approach uses a Systematic Literature Review (SLR) to identify conceptual patterns, research trends, and developments in negotiation theory. The results of the study show that modern negotiation emphasizes the creation of shared value through an integrative approach, strengthening communication, and utilizing digital technology in the decision-making process. In addition, differences in orientation were found between Western negotiation, which is more transactional, and the Indonesian context, which emphasizes relationship harmony and sustainable collaboration. This study provides a theoretical contribution in the form of a comprehensive mapping of the development of the concept of negotiation, as well as practical contributions for business actors in designing effective, adaptive negotiation strategies that are relevant to contemporary business needs.